What ingestions warrant activated charcoal administration?. Issue 8 (August 2017) - Romney, Andrew; Sevdy, Tristan
Abstract : EVIDENCE‐BASED ANSWER : Very few. Activated charcoal does not decrease the length of emergency department or hospital stay, mortality, vomiting, or intensive care unit (ICU) admission in patients with toxic ingestions (SOR: B, single unblinded RCT). Activated charcoal should not be administered routinely, but may be considered if a patient has ingested a potentially toxic amount of a poison known to be absorbed by charcoal, has ingested the substance within 1 hour of presentation, and has a patent or protected airway. Substances not absorbed by activated charcoal include hydrocarbons, acids, and alkalis (SOR: C, expert opinion).